Comparison of PXR Intensity Below and Above the K-edge of Ge; International symposium Radiation from Relativistic electrons in periodic structures RREPS-93, September 6-10, 1993, Tomsk, Russia - Endo I.; Harada M.; Kobayashi T.; Lee Y. S.; Takahashi T.; Yoshida K.; Muto M.; Nitta H.; Potylitsyn A. P. Alexander Petrovich; Zabaev V. N. Viktor Nikolaevich (1993, 1993)
В фонде НТБ ТПУ отсутствует